Optimization and characterization of chia seed (Salvia hispanica L.) oil extraction using supercritical carbon dioxide - Ishak, Izzreen; Hussain, Norhayati; Coorey, Ranil; Abd Ghani, Maaruf (Elsevier, 2021)
Quality of chia seed (Salvia hispanica L.) oil obtained by supercritical carbon dioxide (SC−CO2) is compared with Soxhlet extraction and commercial cold-pressed oil. Response surface methodology (RSM) was conducted to determine the effect of different extraction parameters (pressure, temperature, and grinding time of chia seed) on chia seed oil yield. Linear and quadratic terms of pressure, temperature, and different particle sizes (various grinding times) significantly affected the amount of chia seed oil. The optimal extraction conditions using SC−CO2 to obtain the maximum yield of chia seed oil were as follows: chia seed particle size of 100−400 μm, 24 s of grinding time, extraction pressure of 335 bar and extraction temperature of 45 °C. However, the oil yield of chia seed extracted by SC−CO2 was lower than Soxhlet. Images captured by field emission scanning electron microscopy (FESEM) found a cracked surface in defatted chia seed powders with mostly oil released when high-pressure SC−CO2 is applied. Based on the optimized conditions, chia seed oils obtained by SC−CO2 and Soxhlet had comparable oxidation value, fatty acid composition, thermal properties, tocopherols, and antioxidant activity compared to commercial chia seed oil. However, oxidative stability test shows chia seed oil is less protected against oxidation due to the large amount of polyunsaturated fatty acids (PUFAs) more than 85 %. The present study suggests that SC−CO2 extraction is an effective method to produce chia seed oil with excellent sources of PUFAs and tocopherols.